Counseling Needs of Students at Cagayan State University Philippines: A Framework for the Enhancement of the University Guidance Program - CAMBRI, JONA ADDATU (International Journal of Psychosocial Rehabilitation, 2020)
Students appear to be a vulnerable population whose concerns and needs should be determined and addressed. They experience a multitude of difficulties not only in transitioning but also in coping with the demands of their academics, not to mention the expectations and pressures from their environment. As such, educational institutions are bound to craft and implement policies and programs which are intended to help the at risk group. And should there be policies and programs in place, educational institutions need to continuously monitor and evaluate its efforts.Overall, this study attempts to bring light to the understanding of the counseling needs of students enrolled at Cagayan State University Philippines and its relation on selected personal variables. 400 randomly selected student-respondents took the following measures: Students Needs Inventory; the Panukat ng Katalinuhang Pilipino (PKP) Form A; the 14-Item Resilience Scale; and the Self-Motivation Quiz. Aside from the questionnaires, interview and documentary analysis were also utilized to educe the data needed in the study.The result indicated that the five counseling need areas namely self-development, family relationship, social relationship, academic/studies and specific social issues were all regarded as very important by the students, with the need for self-development being their primary counseling need. The Stepwise Multiple Regression analysis manifested that among the profile variables, age, college, IQ, motivation level, resilience level, and academic performance were correlated to certain counseling need areas. Implications pointed to the importance of revisiting the guidance programme of the University, considering as a substantial input the counseling needs of the students. Efforts to educate the members of the administration, the faculty and other student service providers regarding such findings are likewise indispensable. Further, honing the multicultural competencies of the counselors and educators is indubitably necessary when relating with the student population.